2019
DOI: 10.1093/neuros/nyz313
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extent of Resection on Incidence of Postoperative Complications in Patients With Glioblastoma

Abstract: BACKGROUND Extent of resection (EOR) is well established as correlating with overall survival in patients with glioblastoma (GBM). The impact of EOR on reported quality metrics such as patient safety indicators (PSIs) and hospital-acquired conditions (HACs) is unknown. OBJECTIVE To perform a retrospective study to evaluate possible associations between EOR and the incidence of PSIs and HACs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…The overall morbidity rate was found to reach about 16%. Thereby, the quantitative complication level in our series was in accordance to existent literature where respective values on overall complications in glioblastoma surgery are given between 11 and 32% [ 16 , 21 – 23 ]. It is important to mention that a PSI- and HAC-based assessment of postoperative unfavorable events will also cover transient events like catheter-associated urinary tract infections and therefore will quantitatively surpass complication levels of several previous studies that focused exclusively on postoperative events which required further surgical treatment [ 21 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall morbidity rate was found to reach about 16%. Thereby, the quantitative complication level in our series was in accordance to existent literature where respective values on overall complications in glioblastoma surgery are given between 11 and 32% [ 16 , 21 – 23 ]. It is important to mention that a PSI- and HAC-based assessment of postoperative unfavorable events will also cover transient events like catheter-associated urinary tract infections and therefore will quantitatively surpass complication levels of several previous studies that focused exclusively on postoperative events which required further surgical treatment [ 21 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…Thereby, the quantitative complication level in our series was in accordance to existent literature where respective values on overall complications in glioblastoma surgery are given between 11 and 32% [ 16 , 21 – 23 ]. It is important to mention that a PSI- and HAC-based assessment of postoperative unfavorable events will also cover transient events like catheter-associated urinary tract infections and therefore will quantitatively surpass complication levels of several previous studies that focused exclusively on postoperative events which required further surgical treatment [ 21 , 24 , 25 ]. Further, postoperative secondary hemorrhage and urinary tract infection were identified as the most common unfavorable events within the presented patient cohort of selected temporal glioblastoma disease and observed levels of incidence met previously reported data [ 26 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…[12] Beyond its effect on patient morbidity and mortality, these events are now tracked by regulatory agencies such as the Agency of Healthcare Research and Quality and the Center for Medicare and Medicaid Services as a quality metric to serve as a point of comparison between clinicians and between hospitals. [20] Annual costs related to VTE are estimated to be upwards of 30 billion dollars. [7] Early mobilization, the use of intermittent pneumatic compression devices and chemoprophylaxis is accepted measures to reduce the occurrence of DVT/PE.…”
Section: Discussionmentioning
confidence: 99%
“…Despite tumor location within eloquent brain areas and despite aggressive resections, postoperative complications were lower and neurological outcomes were better following awake resections compared to asleep resections. Previous studies have reported that a greater extent of resection was associated with a lower rate of postoperative complications in glioblastomas [41,49,50] and described the correlation between awake craniotomy and function preservation in series of diffuse gliomas located within eloquent brain areas [51][52][53]. Clavreul et al, showed a correlation between incomplete resection and postoperative neurological deficits in a series of glioblastomas resected under awake craniotomy [42].…”
Section: Discussionmentioning
confidence: 98%